PENGUATAN PENDIDIKAN KARAKTER SISWA SAAT PANDEMI DI SMP ISLAM RAMAH ANAK - Adam Sugiarto (Al-Hasanah : Jurnal Pendidikan Agama Islam, 2021)
Strengthening Student Character (PKS) is a process of forming, accustoming and developing students' abilities to think, behave and behave according to noble religious values and in accordance with the values of Pancasila. Character education is very important for human life, the role of education is not only to show moral knowledge, but also to instill love for students so that they always try to take moral actions. Strengthening Student Character (PKS) in Islamic Junior High School Ramah Anak students is not only carried out in normal conditions but also during a pandemic, where students are required to learn from home (BDR). Strengthening Student Character is carried out as an effort to form and familiarize a good culture in the school and home environment as a manifestation of the Depok City Education Office Program with the theme of Student Character Strengthening Week (PKKS), which is to get better attitudes and behaviors such as independence, mutual cooperation, responsibility. responsible, happy to read, empathetic and caring for the environment. With hope, all students know, understand and apply to every aspect of life, wherever and whenever they are.